Adolescent circadian rhythm disruption increases reward and risk-taking - Lauren M. DePoy; Lauren M. DePoy; Chelsea A. Vadnie; Chelsea A. Vadnie; Chelsea A. Vadnie; Kaitlyn A. Petersen; Kaitlyn A. Petersen; Madeline R. Scott; Madeline R. Scott; Wei Zong; RuoFei Yin; Ross C. Matthaei; et al. (Frontiers in Neuroscience)
IntroductionCircadian rhythm disturbances have long been associated with the development of psychiatric disorders, including mood and substance use disorders. Adolescence is a particularly vulnerable time for the onset of psychiatric disorders and for circadian rhythm and sleep disruptions. Preclinical studies have found that circadian rhythm disruption (CRD) impacts the brain and behavior, but this research is largely focused on adult disruptions. Here, we hypothesized that adolescent CRD would have a greater effect on psychiatric-related behaviors, relative to adult disruption.MethodsWe determined the long-term behavioral and neurobiological effects of CRD during early adolescence by exposing mice to 12 h shifts in the light/dark cycle. Adult mice were exposed to the same CRD paradigm. Behavior testing began approximately 4 weeks later for both groups. To identify possible mechanisms, we also measured gene expression in brain regions relevant to circadian rhythms, mood and reward.ResultsCRD during early adolescence, but not adulthood, persistently increased exploratory drive (risk-taking behavior) and cocaine preference when tested later in life. Interestingly, we found sex differences when intravenous cocaine self-administration was tested. While female mice with a history of adolescent CRD had a greater propensity to self-administer cocaine, as well as increased motivation and cue-induced reinstatement, male adolescent CRD mice had reduced motivation and extinction responding. Importantly, we found that transcripts in the SCN were affected by adolescent CRD and these were largely distinct across sex.ConclusionOverall, adolescent CRD in mice caused persistent increases in risky behavior, cocaine reward and cocaine self-administration, which suggests that CRD during adolescence may predispose individuals toward substance use disorders. Future research is required to elucidate how adolescent CRD affects behaviors relevant to mood-and substance use-related disorders across the 24-h day, as well as to identify intervention strategies to alleviate disruption during adolescence and novel therapeutic approaches once symptoms have begun.